An examination of the impact of compliance with internal audit standards on financial reporting quality: Evidence from Saudi Arabia. Issue 3 (2nd September 2019) - Alzeban, Abdulaziz
Abstract : Purpose: The purpose of this study is to explore the impact of internal audit (IA) compliance with the International Standards for the Professional Practice of Internal Auditing (ISPPIA) on financial reporting quality (FRQ). Design/methodology/approach: Data were gathered from 142 chief audit executive from Saudi listed companies, and also from the annual reports of the participating companies. Two proxies are used to measure FRQ, namely, discretionary accruals and accruals quality. Findings: The findings reveal that companies demonstrating higher IA compliance with standards have better FRQ. They also indicate that the interaction between IA competency and its compliance with standards has an impact on FRQ. Further, the findings provide evidence that FRQ is higher in companies where IA departments have formal documentation, that is, entirely consistent with the ISPPIA. These results retain their robustness after further analysis. Originality/value: In offering these findings, the paper contributes to the existing IA literature by introducing evidence from a Middle Eastern context, namely, Saudi Arabia, of the link between IA compliance with the ISPPIA and FRQ. It confirms the role of IA in FRQ, and hence, as an element of corporate governance, information, which is valuable for both the institute of internal auditors and companies.